Antioxidative Characteristics of Chicken Breast Meat and Blood after Diet Supplementation with Carnosine, L-histidine, and β-alanine - Wieslaw Kopec; Dorota Jamroz; Andrzej Wiliczkiewicz; Ewa Biazik; Anna Pudlo; Malgorzata Korzeniowska; Tomasz Hikawczuk; Teresa Skiba (MDPI AG, 2020)
The objective of the study was to test the effect of diets supplemented with β-alanine, L-histidine, and carnosine on the histidine dipeptide content and the antioxidative status of chicken breast muscles and blood. One-day-old Hubbard Flex male chickens were assigned to five treatments: control diet (C) and control diet supplemented with 0.18% L-histidine (ExpH), 0.3% β-alanine (ExpA), a mix of L-histidine\β-alanine (ExpH+A), and 0.27% carnosine (ExpCar). After 28 days, chicken breast muscles and blood samples were analyzed for the antioxidant enzyme activity (catalase (CAT), glutathione peroxidase (GPx), superoxide dismutase (SOD)), carnosine and anserine content, amino acid profile, and anti-radical activity (ABTS, DPPH, ferric reducing antioxidant power (FRAP)). The results of the study showed that carnosine supplementation effectively increased body weight and breast muscle share in chicken carcasses. Carnosine and L-histidine supplementation with or without β-alanine increased carnosine content in chicken breast muscles up to 20% (p = 0.003), but the boost seems to be too low to affect the potential antioxidant capacity and amino acid content. The β-alanine-enriched diet lowered dipeptide concentration in chicken blood serum (p = 0.002) and activated catalase in chicken breast muscles in relation to the control group (p = 0.003). It can be concluded that histidine or dipeptide supplementation of chicken diets differently affected the total antioxidant potential: in breast muscles, it increased dipeptide content, while in blood cell sediment (rich in erythrocytes), increased SOD and GPx activities were observed.